A test of the cumulative effect of river weirs on downstream migration success, speed and mortality of Atlantic salmon (Salmo salar) smolts: An empirical study. Issue 1 (16th August 2018) - Newton, Matthew; Barry, James; Dodd, Jennifer A.; Lucas, Martyn C.; Boylan, Patrick; Adams, Colin E.
Abstract: This study investigated the cumulative impact of weirs on the downstream migration of wild Atlantic salmon ( Salmo salar ) smolts in the River Foyle, Northern Ireland. In spring of 2013 fish were released in two tributaries of similar length; one tributary (impacted) had seven low‐head weirs along the migration pathway and the other was devoid of such structures (un‐impacted). Salmon smolts fitted with acoustic transmitters were monitored via a passive acoustic telemetry array during downstream migration. In 2014 the study was repeated only in the impacted tributary. Overall freshwater survival rates were high (>94%). There was no significant difference in mortality, movement pattern, delay or travel speeds between rivers or between years at any phase of migration. Escapement of salmon smolts through Lough Foyle (a marine sea lough) to the open ocean was low, approximately 18% in each year. Escapement did not differ between impacted and un‐impacted rivers. This study showed no postpassage effects of weirs on mortality, migration speed or escapement of downstream migrating smolts. This suggests that the elevated mortality at low‐head obstacles described in other studies is not inevitable in all river systems. Migration through rivers with natural riffle‐pool migration may result in similar effects as those from low‐head weirs. Causes of apparent high mortality in the early part of marine migration in this study, are unknown; however similar studies have highlighted the impact of fish predators on smolts.